Increase in neuropsychiatric symptoms after occupational exposure to low levels of styrene. Issue 9 (September 1993) - Edling, C; Anundi, H; Johanson, G; Nilsson, K
Abstract : The results of this study suggest that exposure to styrene below the current Swedish permissible exposure limit of 20 ppm induces neurotoxic effects expressed as an increased number of neuropsychiatric symptoms. Twenty men exposed to styrene at a plastics factory participated. The reference group included 20 non-exposed men matched for age, working schedule, and physical work load. Exposure to styrene during one workday was assessed by personal air monitoring and biological monitoring. To evaluate the physical work load the pulse(heart) rate was measured. One week before the study each man completed a neuropsychiatric symptom questionnaire containing 16 items. Also 17 questions regarding acute symptoms of local irritation and symptoms of the central nervous system were presented after the psychometric tests were performed. The tests were simple reaction time, colour word vigilance, and symbol digit. A follow up with regard to the symptoms among the exposed men was done after their summer vacation, about two to five weeks after their last exposure. The mean eight hour time weighted average (TWA) concentration of styrene in air, measured by passive dosimetry was 8.6 ppm (range 0.04-50.4 ppm). The exposed men had significantly more symptoms than the referents although there were no significant differences for the psychometric tests. At the follow up the exposed men reported fewer symptoms. This study indicates that symptoms are earlier indicators of adverse effects than complex tests and underlines the importance of regular follow up of people exposed to styrene (and probably organic solvents in general).